Development and Implementation of Next Generation Molecular Tool Kits for Environmental Applications - Berry, Tina Elizabeth (Curtin University, 2019)
Environmental DNA (eDNA) is used increasingly to map biodiversity in both marine and terrestrial ecosystems. In this thesis, a combination of existing and novel eDNA assays are used to study temporal and spatial patterns in; scat—from the Australian sea lion (Neophoca cinerea)—and Australian plankton samples. In the context of a rapidly changing environment, and a variety of anthropogenic pressures, this thesis demonstrates the role eDNA can play in monitoring and managing marine biodiversity.